Penerapan Terapi Bermain Finger Painting Untuk Meningkatkan Perkembangan Motorik Halus pada Anak Usia Prasekolah: Case Series - Apriana, Rista; Taludio, Lisa Aisyiah; Adam, Lusiane (Journal Nursing Care Jurusan Keperawatan Politeknik Kesehatan Gorontalo, 2025)
Background: Preschool children aged 4-6 years, are expected to have mastered various fine motor skills. Fine motor skills involve movements that engage specific parts of the body using fine muscles, such as the skills involving finger movements and precise wrist actions. One way to improve children's fine motor development is through finger painting play. The application of finger painting play therapy is an effective stimulus for improving fine motor skills. Finger painting involves painting with fingers, where children apply colors directly onto paper or other media. Objective: It aims to determine the results of the application of finger painting play therapy in children aged 4-6 to improve fine motor skills. Method: This case study used a descriptive approach, guiding the author to review the effectiveness of finger painting play therapy in improving fine motor skills in children aged 4-6 years. Results: The case study results showed a difference between pre-test and post-test scores, indicating an improvement in scores after the finger painting play activity. Unconsciously, children actively learn to use their fingers. Conclusion: The application of finger painting play therapy is effective in improving fine motor skills in children aged 4-6 years.